1997
DOI: 10.1063/1.364078
|View full text |Cite
|
Sign up to set email alerts
|

ZnS:Tm grown by metalorganic chemical vapor deposition with Cl codoping

Abstract: ZnS:Tm and ZnS:Tm,Cl thin films were grown by metalorganic chemical vapor deposition (MOCVD), using diethylzinc, H2S, Tm(thd)3 (thd=2,2,6,6-tetramethyl-3,5-heptanedione), and HCl. The ZnS:Tm did not contain oxygen which might be introduced through the thd-radical. It thus has only codopant-free Tm3+ luminescent centers probably associated with native defects. The electroluminescence (EL) spectrum of the ZnS:Tm,Cl showed three satellite emission lines in addition to the original emission of the ZnS:Tm, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Kato et al, reported that the 1 G 4 ! 3 H 5 transitions of Tm 3+ is quenched due to the existence of ion-pair relaxation between Tm 3+ ions in the MOCVD-grown ZnS thin film at high (over 1 mol%) Tm concentrations [10]. Thus, the high Tm concentrations from 1 to 15 mol% of our TFEL devices are responsible for quenching of the 1 G 4 !…”
Section: Discussionmentioning
confidence: 88%
“…Kato et al, reported that the 1 G 4 ! 3 H 5 transitions of Tm 3+ is quenched due to the existence of ion-pair relaxation between Tm 3+ ions in the MOCVD-grown ZnS thin film at high (over 1 mol%) Tm concentrations [10]. Thus, the high Tm concentrations from 1 to 15 mol% of our TFEL devices are responsible for quenching of the 1 G 4 !…”
Section: Discussionmentioning
confidence: 88%
“…In addition to the above cation substitution, anion substitution is also an effective method to improve the decomposition properties of complex hydrides. Since the ionic radius of fluorine anions (F – , 1.36 Å) is quite close to the ionic radius of hydrogen anions (H – , 1.37 Å), the partial substitution of F – for H – in LiBH 4 is possible. For example, Gosalawit-Utke et al reported that the kinetics of a 2LiF/MgB 2 –H 2 system is significantly improved due to the formation of some hydridofluoride phases (LiBH 4– x F x and LiH 1– y F y ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the above cation substitution, anion substitution is also an effective method to improve the decomposition properties of complex hydrides. 22À26 Since the ionic radius of fluorine anions (F À , 1.36 Å) 27 is quite close to the ionic radius of hydrogen anions (H À , 1.37 Å), 28 the partial substitution of ABSTRACT: A 3LiBH 4 /MnF 2 composite was prepared by mechanically milling a mixture of LiBH 4 and MnF 2 . The decomposition properties of the 3LiBH 4 /MnF 2 composite were investigated and compared with those of the 3LiBH 4 /MnCl 2 composite.…”
Section: Introductionmentioning
confidence: 99%
“…However, lanthanide hydrides as reactants working on the dehydrogenation process of NaBH 4 have not been investigated yet. In addition, though the uorine anion (F À , 1.36 Å) 27 and the hydrogen anion (H À , 1.37 Å) 28 have similar ion radii and the same valence of À1, metal uorides usually show superior performance to the same metal hydrides as additives. For instance, TiF 3 exhibited superior catalytic effects than TiH 2 on the dehydrogenation of MgH 2 (ref.…”
Section: Introductionmentioning
confidence: 99%